TOPIC: BUSINESS MODEL PROPOSITION BASED ON THE PRODUCTION OF HIGH ADDED VALUE PRODUCTS MADE BY THE REPROCESSING OF WASTED TIRES LOCATED AT THE MAJOR TIRE COMMERCIAL HOUSES IN GUAYAQUIL. - Raad Serrano, Ernesto Nicolás (2014)
This research couples the necessity of recycling tires in Ecuador along with the opportunity of starting a waste tire recycling businesses in Guayaquil, Ecuador, South America. The research takes into account various international solutions to the problem of used tires, specifically highlighting the legislation and macro structure of the waste tire industry in Australia and USA. The industry structure of molded rubber in which benefits from a macro waste tire recycling project will allow for the potential of Ecuadorian expertise. The current Ecuadorian situation on tire recycling is reviewed in this paper. The Ecuadorian government is moving forward into making the country suitable for having a sustainable tire recycling industry. Legislation has been approved supporting future recycling projects but it is still only the foundation stage. This paper also analyzes the current situation of the waste tire recycling environment in Guayaquil concluding that it is still in a developing stage. Finally, the research proposes a waste tire recycling business dedicated to the shredding of scrap tires and devulcanization of scrap tire powder. Using the devulcanized powder as 80% of the raw material needed for the final product, the production process meets a relative low cost, suitable quality solution. The final product is rubber mats for the cow owners mainly in Manta, Ecuador. The business project considers and includes the recycling legislation foundation to affirm a complete government guarantee on free of cost supply of waste tires all year round as Environmental Manager as end of life waste tire consumers. The proposed business project concludes that with proper regulation, a waste tire devulcanization plant in Guayaquil can be economically feasible and sustainable over time. It will even attract significant capital to invest on the industry because of its potential profitability which will allow for increased employment and international recognition as a enviro-friendly country